Jurnal Penyuluhan: Strategi Pengembangan Perilaku Komunikasi Guru Responsif Gender - Ernita Arif, Aida Vitayala S Hubeis, Basita Ginting Sugihen, Ninuk Purnaningsih, Amiruddin Saleh (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
The teacher is a strategic factor in the learning process. For that teachers must have good skills, especially the ability to communicate, because the whole learning process is closely related to communication.